A randomised controlled trial of a complex intervention to reduce children's exposure to secondhand smoke in the home. Issue 2 (21st April 2017) - Ratschen, Elena; Thorley, Rebecca; Jones, Laura; Opazo Breton, Magdalena; Cook, Juliette; McNeill, Ann; Britton, John; Coleman, Tim; Lewis, Sarah
Abstract : Objectives: Exposing children to secondhand tobacco smoke (SHS) causes significant harm and occurs predominantly through smoking by caregivers in the family home. We report a trial of a complex intervention designed to reduce secondhand smoke exposure of children whose primary caregiver feels unable or unwilling to quit smoking. Design: An open-label, parallel, randomised controlled trial. Setting: Deprived communities in Nottingham City and County, England Participants: Caregivers resident in Nottingham City and County in England who were at least 18 years old, the main caregiver of a child aged under 5 years living in their household, and reported that they were smoking tobacco inside their home. Interventions: We compared a complex intervention combining personalised feedback on home air quality, behavioural support and nicotine replacement therapy for temporary abstinence with usual care. Main outcomes: The primary outcome was change in air quality in the home, measured as average 16–24  hours levels of particulate matter of  < 2.5  µm diameter (PM2.5 ), between baseline and 12 weeks. Secondary outcomes included changes in maximum PM2.5, proportion of time PM2.5 exceeded WHO recommended levels of maximum exposure of 25  µg/mg 3, child salivary cotinine, caregivers' cigarette consumption, nicotine dependence, determination to stop smoking, quit attempts and quitting altogether during the intervention. Results: Arithmetic mean PM2.5 decreased significantly more (by 35.2 %; 95%  CI 12.7% to 51.9 %) in intervention than in usual care households, as did the proportion of time PM2.5 exceeded 25  µg/mg 3, child salivary cotinine concentrations, caregivers' cigarette consumption in the home, nicotine dependence, determination to quit and likelihood of having made a quit attempt. Conclusions: By reducing exposure to SHS in the homes of children who live with smokers unable or unwilling to quit, this intervention offers huge potential to reduce children's' tobacco-related harm. Trial registration number: ISRCTN81701383. This trial was funded by the UK National Institute for Health Research (NIHR): RP-PG-0608-10020